Tindak Tutur Ekspresif dan Strategi Bertutur Guru dalam Pembelajaran Bahasa Indonesia Kelas VIII SMP Negeri 41 Padang - Putri, Dinda; Noveria, Ena (Al-DYAS, 2023)
The purpose of this research is twofold. First, the forms of expressive speech acts used by Indonesian language teachers in the learning process for class VIII SMP Negeri 41 Padang. Second, the speaking strategy used by Indonesian language teachers in the process of learning Indonesian for class VIII SMP Negeri 41 Padang. This type of research is a qualitative research with descriptive method. The results of this study are twofold. First, there are five forms of expressive speech acts for teachers in learning Indonesian in class VIII SMP Negeri 41 Padang, (1) expressive speech acts of apologizing, (2) expressive speech acts of praising, (3) expressive speech acts of blaming, (4) expressive speech acts expressive criticizing, and (5) expressive speech act of thanking. Second, the teacher's speaking strategy in learning Indonesian for class VIII SMP Negeri 41 Padang there are four, (1) the strategy of speaking frankly without further ado, (2) the strategy of speaking frankly with pleasantries of positive politeness, (3) the strategy of speaking directly clear with negative politeness pleasantries, and (4) vague speaking strategies. Based on the results of the study, it was concluded that there were five forms of expressive speech acts by teachers in Indonesian language learning class VIII SMP Negeri 41 Padang, and there were also four teacher speech strategies in learning Indonesian for class VIII SMP Negeri 41 Padang.